How to Make Innovation Happen in ASOG Shanghai - Ding, Haohong (2012)
Public hospitals dominate the healthcare marketplace in China, while private facilities are smaller with more limited service offerings. The physical environment of these public hospitals is often characterized by inadequate hygiene, non-patient friendly design and a lack of privacy. As incomes rise under a predominantly fee-for-service system, patients with income power are able to choose more costly private healthcare facilities. The only way for private hospitals to excel is to develop the capability to offer innovative services to win this niche market. This paper focuses how to make innovation happen in ASOG shanghai, which studies the innovation target, innovative capacities and innovation implementation. ASOG recruits and develops the professional team with sufficient clinic experience, encourages them to implement innovation through high levels of innovative capacity with the strong government partnership and high employee participation. In the same time, ASOG control the innovation cost and risk effectively based on the strong private-public partnership. After running several years according to this innovation model successfully, ASOG will turn to be a spiritual soother for the patients.